Human resource management demystified - DelCampo, Robert G. (DeMYSTiFieD series, 2011)
The low-labor guide to mastering HRM! Want to dive into human resources but your brain says, "Help wanted!"? No problem! Put Human Resource. Management DeMYSTiFieD on the job, and you'll solve your dilemma in no time! Using a clear, step-by-step format, this practical guide provides a firm foundation in the basics of the field. You'll master all the key issues in human resources, like benefits, legal situations, hiring, training, outplacement, worker rights, and more. Detailed examples and concise explanations make it easy to grasp the material, and end-of-chapter quizzes and a final exam help reinforce learning. In no time, you'll build a firm foundation on the essential concepts and techniques instrumental to the success of any organization! This fast and easy guide features: Tips on designing and implementing a hiring plan; Tactics for developing and training new employees; Strategies for writing job descriptions, recruiting applicants, and selecting employees; Techniques for creating an effective compensation and benefits structure; Simple enough for a beginner, but challenging enough for an advanced student, Human Resource Management DeMYSTiFieD has everything you need to build a solid foundation in human resources.